Cryptomoschatone D2 from Cryptocarya mandioccana: cytotoxicity against human cervical carcinoma cell lines - Soares, Christiane Pienna [UNESP]; Giocondo, Maísa Pasquotto [UNESP]; Bassi, Carmen Lúcia; Telascrea, Marcelo [UNESP]; Cavalheiro, Alberto José [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Agustoni, Daniele [UNESP]; Mello, Elaine Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Among the substances isolated from Cryptocarya sp, some styrylpyrones, such as goniothalamin, demonstrate antiproliferative activity in a broad range of human cell lines. In the present study, we assessed the cytotoxicity of a styrylpyrone (cryptomoschatone D2), isolated from Cryptocarya mandiocanna, in HPV-infected (HeLa and SiHa) and uninfected (C33A) human cervical carcinoma cell lines and a human lung fibroblast line (MRC-5). The cytotoxicity was tested by the MTT assay. In this assay, cells were treated with cryptomoschatone D2 at 15, 30, 60 or 90 μM for 6, 24 or 48 hours, as well as for 6 hours followed by a post-treatment recovery period of 24, 48 or 72 hours. High cytotoxicity (dose- and timedependent) was observed in HeLa, SiHa, C33A and MRC-5 cell lines. Although in general the styrylpyrone cytotoxicity was not significantly different among the cell lines tested, it was apparently stronger in HeLa and C33A than in MRC-5 and SiHa in the 24 or 48-hour treatments. Moreover, HeLa and SiHa were able to recover their ability to proliferate, in direct proportion to the post-treatment recovery time. On the other hand, C33A did not demonstrate a similar post-treatment recovery. We can conclude that cryptomoschatone D2 possesses high dose-dependent or time-dependent cytotoxicity. Keywords: Cell culture. Antiproliferative activity. Styrylpyrone, Cryptomoschatone D2. RESUMO Cryptomoscatona D2 de Cryptocarya mandioccana: atividade citotóxica contra linhagem celular de carcinoma cervical humano Dentre as substâncias isoladas de Cryptocarya sp, algumas estirilpironas, como a goniotalamina, apresentam atividade antiproliferativa em diferentes linhagens celulares. No presente estudo, foram avaliadas as atividades citotóxica de uma estirilpirona (criptomoscatona D2) isolada de Cryptocarya mandiocanna, em linhagens celulares de carcinoma cervical humano infectada por HPV (HeLa e SiHa), não infectada (C33A) e fibroblasto pulmonar humano (MRC-5). A atividade citotóxica foi avaliada pelo ensaio do MTT. No ensaio do MTT, as células foram tratadas com criptomoscatona D2 em 15, 30, 60 e 90 μM por 6, 24 e 48 horas e por 6 horas com período de recuperação de 24, 48 e 72 horas pós-tratamento. O tratamento com a estirilpirona (criptomoscatona D2) ocasionou elevada citotoxicidade dose-resposta e tempo-resposta em HeLa, SiHa, C33A e MRC-5. Embora não haja diferença estatisticamente significativa de citotoxicidade entre as linhagens, aparentemente a citotoxicidade foi maior em HeLa e C33A (tratamento de 24 e 48 horas) que em MRC-5 e SiHa. Ainda, no período de recuperação, HeLa e SiHa aparentemente restabelecem sua capacidade proliferativa, que é diretamente proporcional ao tempo de recuperação, enquanto o mesmo comportamento não é observado em C33A. Estes resultados sugerem que criptomoscatona D2 possui elevada atividade antiproliferativa dose-resposta ou o tempo resposta. Palavras-chave: Cultura celular. Atividade antiproliferativa. Estirilpirona. Criptomoscatona D2.
Keywords: Farmácia; Análises Clínicas; citotoxicidade; Cryptocaria mandioccana; MTT; citotoxicicidade em linhagens celulares humanas